2021
DOI: 10.1097/eja.0000000000001611
|View full text |Cite
|
Sign up to set email alerts
|

Effects of methylene blue on microcirculatory alterations following cardiac surgery

Abstract: BACKGROUND Methylene blue is used as rescue therapy to treat catecholamine-refractory vasoplegic syndrome after cardiac surgery. However, its microcirculatory effects remain poorly documented.OBJECTIVE We aimed to study microcirculatory abnormalities in refractory vasoplegic syndrome following cardiac surgery with cardiopulmonary bypass and assess the effects of methylene blue.DESIGN A prospective open-label cohort study.SETTING 20-Bed ICU of a tertiary care hospital.PATIENTS 25 Adult patients receiving 1.5 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
(133 reference statements)
0
2
0
Order By: Relevance
“…It was found that microcirculatory is still abnormal despite normalization of blood pressure by vasopressors under this condition, which is considered the primary cause of kidney and hepatic dysfunction, and cardiac injury after the operations. 23 Methylene blue has been suggested as an adjuvant treatment in the setting of refractory hypotension. 24,25 Methylene blue reduces nitric oxide-mediated vasodilation via direct inhibitory of iNOS and soluble guanylate cyclase, 26 which attenuates remarkably low response to vasoconstrictor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that microcirculatory is still abnormal despite normalization of blood pressure by vasopressors under this condition, which is considered the primary cause of kidney and hepatic dysfunction, and cardiac injury after the operations. 23 Methylene blue has been suggested as an adjuvant treatment in the setting of refractory hypotension. 24,25 Methylene blue reduces nitric oxide-mediated vasodilation via direct inhibitory of iNOS and soluble guanylate cyclase, 26 which attenuates remarkably low response to vasoconstrictor.…”
Section: Discussionmentioning
confidence: 99%
“…Methylene blue is recommended as an effective treatment of refractory hypotension which is not sensitive to catecholamine in the international guidelines. 27 Recently, it has been reported that methylene blue improved both macro-circulation and micro-circulation, and thus attenuates mismatch between macro-circulation and micro-circulation induced by administration with high dose of catecholamine, 23 which was regarded to contribute to improve hepatic and kidney function, and attenuated myocardium ischemic damage. It has been reported that methylene blue is routinely administrated as rescue therapy for catecholamine-refractory hypotension in the setting of cardiac surgery, sepsis shock, and liver transplantation.…”
Section: Discussionmentioning
confidence: 99%